1974
DOI: 10.1002/dev.420070105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype and practice upon behavioral development in mice

Abstract: Psychomotor development from birth to 18 days of, age was observed in 3 Lines of mice selected for high (H), medium (M), and low (L) brain weight. Litters were cut to 8 at birth and half of the individuals randomly assigned to a practiced group tested daily; the remainder were assigned to a nonpracticed group and were tested only on selected tests on the day at which their littermates met a predesignated criterion. Significant differences between the lines were found in open field activity, balancing on a roto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1

Year Published

1975
1975
1998
1998

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 13 publications
4
27
1
Order By: Relevance
“…Similar to the results of Fuller and Herman (1974) which suggested a high degree of concordance among the BWS lines with respect to brain weight and psychomotor maturation, the present data indicate that H-line mice show within-session improvement of correct choice-point turns as well as 24-hr retention of that training at an earlier age than do the M-and L-lines. In addition, M-and Lline mice with similar brain growth functions first demonstrate within-session improvement in correct turns at the same age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the results of Fuller and Herman (1974) which suggested a high degree of concordance among the BWS lines with respect to brain weight and psychomotor maturation, the present data indicate that H-line mice show within-session improvement of correct choice-point turns as well as 24-hr retention of that training at an earlier age than do the M-and L-lines. In addition, M-and Lline mice with similar brain growth functions first demonstrate within-session improvement in correct turns at the same age.…”
Section: Discussionsupporting
confidence: 90%
“…The importance of genic factors in influencing maturation has also been suggeste-d by investigations involving ontogenetic behavioral comparisons among strains of mice (Groswald & Luttges, 1975;Meier, 1964;Nagy, Misanin, & Wetzel, 1973), though relatively few studies have utilized this approach. Recent research using a 3rd genetic technique has demonstrated that in mice genetically selected for differences in brain weight, genes regulating brain growth also influence behavioral development (e.g., Fuller &Herman, 1974).Results of experiments from 2 brain-weight selection programs, created to explore a number of genetically based brain-behavior relationships in both neonatal and adult mice, …”
mentioning
confidence: 99%
“…The Fuller lines were genetically selected for differential brain size; they include a high line (H), a low line (L), and a medium line (M) (Fuller & Herman, 1974). The H and L lines were chosen for this experiment because they exhibit differential rates of neural and behavioral development (Fuller & Herman, 1974;.…”
Section: Subjectsmentioning
confidence: 99%
“…With relatively small samples the significance of the relationship was not found in all comparisons, but there were no examples of relationships in the opposite direction. The earlier decline of ASV in Lmice is associated with lower weight and slower development of motor skills (Fuller & Herman, 1974) and is consonant with such a hypothesis.…”
Section: Discussionmentioning
confidence: 76%